A bidirectional double uneven power converter based dc–dc converter for solid-state transformers - Park, Kiwoo; Lee, Kyo Beum (Electronics (Switzerland), 2018)
This paper presents a novel bidirectional double uneven power (BiDUP) based dc-dc converter and its design and control methods. The proposed converter utilizes two dual active bridge (DAB) converters with different power ratings in a special way to realize zero current switching (ZCS), where both turn-on and turn-off switchings occur under the zero-current condition. A design example of the proposed BiDUP converter is presented for medium voltage (MV) and high-power solid-state transformer (SST) systems where both voltage transformation and bidirectional power flow are required. The main features of the proposed converter are to reduce both the switching losses in power semiconductor devices and the filter inductance requirement simultaneously. To verify the feasibility of the proposed converter, a simulation study on the BiDUP converter based SST in a distribution system is presented. Furthermore, to validate the operational principle of the proposed converter, an experimental study using a small-scale prototype is also presented.
Keywords: Dc-dc converter; Power electronic transformer; Solid-state transformer; Zero current switching (ZCS)